2018
DOI: 10.1002/cyto.b.21642
|View full text |Cite
|
Sign up to set email alerts
|

Platelet characteristics in patients with essential thrombocytosis

Abstract: The study showed that ET patients compared to healthy individuals have an increased amount of reticulated platelets and increased aggregation potential. These findings might in part explain the increased thromboembolic risk in patients with ET. © 2018 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…Impedance aggregometry results were compared with data on healthy controls chosen to match ECMO patients on two ranked criteria: (a) gender; (b) age. Data on healthy controls for ADP and AA induced platelet aggregation were obtained from Rubak et al (28) and data on TRAP induced platelet aggregation were obtained from Pedersen et al (35).…”
Section: Methodsmentioning
confidence: 99%
“…Impedance aggregometry results were compared with data on healthy controls chosen to match ECMO patients on two ranked criteria: (a) gender; (b) age. Data on healthy controls for ADP and AA induced platelet aggregation were obtained from Rubak et al (28) and data on TRAP induced platelet aggregation were obtained from Pedersen et al (35).…”
Section: Methodsmentioning
confidence: 99%
“…25 Platelet aggregation measured by impedance aggregometry is known to be positively associated with platelet count. 26,27 Indeed, when platelet aggregation results were divided by platelet count, the difference in antiplatelet effect of aspirin during 24 hours was no longer present indicating that the significantly higher aggregation found could, at least in part, be explained by the higher platelet count in ET patients. However, simply dividing platelet aggregation with platelet count is an imperfect way of adjusting for high platelet count, although studies found a linear relationship between platelet count up to 700 Â 10 9 /L and platelet aggregation.…”
Section: Discussionmentioning
confidence: 98%
“…[ 18 ] Previous studies showed that circulating platelet-leukocyte aggregates are found to more frequent in ET patients with thrombosis. [ 7 ] ET patients with JAK2 mutation have an increased risk of venous and arterial thrombosis. [ 19 ] Furthermore, the occurrence of mucosal and gastrointestinal bleeding was likely due to the inverse relationship between platelet and von Willebrand factor.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 6 ] Essential thrombocytosis is associated with an increased risk of thromboembolic events. [ 7 ] Thrombotic and vascular complications are the chief causes of death in patients with essential thrombocytosis. [ 8 ] In this case, the Korean patient had developed multiple cerebral arterial thrombosis at postoperative day 1 after carotid endarterectomy (CEA).…”
Section: Introductionmentioning
confidence: 99%